The Use of WhatsApp in Reading Lesson at the STMIK Pontianak, West Kalimantan, Indonesia - Susanti, Susanti (Universitas Pendidikan Indonesia, 2020)
ABSTRACT: The aim of this study is to figure out the effects of WhatsApp mobile learning in teaching reading to students in the 2nd semester of Informatics Technique Program at the STMIK (College of Computer Science Management) Pontianak, West Kalimantan, Indonesia. Experimental study is the research design applied to figure out more the effect of WhatsApp usage by the learners in reading lesson. The classes are grouped into experimental and control groups. Students in experimental group have additional learning activities, besides the normal class in the classroom, that is additional learning using WhatsApp mobile learning; but students in control group just have the normal class as usual in the classroom. Questionaires, WhatsApp platforms, and Pre-post tests become the sources of data collection used. The results indicatedÂ that WhatsApp mobile learning usage in learning reading skill to the 2nd semester students of Informatics Technique Program at the STMIK Pontianak shows an insignificant results of this study. So, it is needed to support from other institutions for the ease and decent WiFi (Wireless Fidelity) access for using WhatsApp in mobile phone assisted learning.KEY WORD: Mobile Phone Assisted Learning; Reading Lesson; Using WhatsApp.Â ABSTRAKSI: â€œPenggunaan WhatsApp dalam Pelajaran Membaca di STMIK Pontianak, Kalimantan Barat, Indonesiaâ€. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh aplikasi â€œWhatsAppâ€ pada telefon genggam didalam pembelajaran membaca pada mahasiswa Program Teknik Informatika semester 2 di STMIK (Sekolah Tinggi Manajemen Ilmu Komputer) Pontianak. Studi eksperimen adalah desain penelitian yang digunakan untuk mengetahui lebih jauh pengaruh penggunaan â€œWhatsAppâ€ oleh para mahasiswa dalam pelajaran membaca. Kelas dikelompokkan menjadi kelas eksperimen dan kelas kontrol. Para mahasiswa di kelas eksperimen mempunyai aktivitas belajar tambahan, selain belajar rutin di kelas, yaitu tambahan belajar menggunakan aplikasi â€œWhatsAppâ€ pada telefon genggam; tetapi para mahasiswa di kelas kontrol hanya belajar seperti pada umumnya didalam kelas. Kuestioner, program â€œWhatsAppâ€, dan pra-pasca tes menjadi sumber pengumpulan data. Hasil penelitian menunjukkan bahwa penggunaan â€œWhatsAppâ€ pada telefon genggam dalam pembelajaran keterampilan membaca pada mahasiswa semester 2 Program Teknik Informatika di STMIK Pontianak menunjukkan hasil yang tidak memuaskan. Jadi, diperlukan dukungan dari lembaga lain untuk kemudahan dan akses WiFi (Jaringan Internet) untuk menggunakan â€œWhatsAppâ€ dalam pembelajaran berbantukan telefon genggam. KATA KUNCI: Pembelajaran Berbantukan Telefon Genggam; Pelajaran Membaca; Penggunaan â€œWhatsAppâ€.About the Author: Susanti, M.Pd. is a Lecturer of Information System at the STMIK (Sekolah Tinggi Manajemen Ilmu Komputer or College of Computer Science Management) Pontianak, Jalan Merdeka Barat No.372, Kota Pontianak, West Kalimantan, Indonesia. For academic interests, the Author is able to be contacted via e-mail address at: santy.mayfoura@gmail.comÂ Suggested Citation:Â Susanti. (2020). â€œThe Use of WhatsApp in Reading Lesson at the STMIK Pontianak, West Kalimantan, Indonesiaâ€ inÂ MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 5(1), March, pp.57-74. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online).Article Timeline: Accepted (January 9, 2020); Revised (February 28, 2020); and Published (March 30, 2020).